User Experience & Human Centred Design for a blockchain based provenance traceability platform - Chehore, Thandeka (School of Economics, 2023)
The study measures the usability of a live prototype of an early stage Blockchain based food provenance application named Food Print. The aim is to see the effect of human centred design principles on the user's engagement with, and the perception of the application. This study describes a human-centred design approach to designing an early stage blockchain based supply chain web application, which is aimed at improving user engagement at a farmer's market. Design thinking and user experience design frameworks are used to guide the process of researching, analysing, designing, building and testing the prototype. A user interface is designed and deployed to see how the users perceive the value of the web application-based user experience design. With the assistance of Oranjezicht City Farm market management team, the researcher carries out user experience research based on design thinking principles. The purpose is to create the first iteration of supply chain application that provides insight into the provenance of the fresh produce. The study is on human-centred design principles with a focus on user experience and engagement. User experience and design thinking methodologies form the basis of the study. The study involves surveys and observations that result in two user personas that are used for the design and prototyping of the high fidelity application. The deliverable for this study is a high fidelity prototype for a fresh produce provenance application that uses blockchain technology. It is accompanied by usability testing focusing on the perceived value and usability of the early stage blockchain based application